ISO/IEC 38500 : the IT governance standard - Calder, Alan, 1957- (IT Governance Publishing, 2008)
The emergence of ISO/IEC 38500 the international standard for the corporate governance of information and communication technology puts boards around the world in a position from which they can take effective action to apply core governance principles to their information and communication technology.